FIELD INVESTIGATIONS AND LABORATORY SIMULATION OF CLOGGING IN LIXI TAILINGS DAM OF JINDUICHENG, CHINA - Wu Ju.; Wu Ya.; Lu J.; Lee L. (My University, 2007)
Clogging is one of the most important factors affecting the stability of the tailings dams. Firstly, this work investigates the clogging materials of Lixi tailings dam using ICP-AES, X-ray powder diffraction (XRD) and SEM analysis methods. The ICP-AES results indicate that Fe is the dominant element in the clogging materials. The iron contents of clogging samples collected from 2# radial-well pipe and the access hole of the starter dam are 54.35 and 40.24%, respectively. XRD spectra show that ferric hydroxide is the main initial component of the clogging materials. Other compounds such as akaganeite, hematite and goethite are products from ferric hydroxide transformation. Therefore, the clogging materials are a mixture of ferric hydroxide and its converted products. The clogging materials commonly exist in an amorphous form with a cluster microstructure when viewed under SEM. Secondly, this work uses a continuous flow column to simulate clogging in the laboratory, and the clogging materials are analyzed with XRD and SEM. The chemical analysis indicates that the iron content of the clogging materials from the experiment is 45.43%. XRD spectra show that hematite is the only compound detected. The clogging materials generated experimentally are also in amorphous cluster microstructure when viewed under SEM.
Keywords: TAILINGS DAM; CLOGGING; IRON COMPOUNDS; EXPERIMENT ANALYSIS